2002
DOI: 10.1103/physrevlett.88.057403
|View full text |Cite
|
Sign up to set email alerts
|

Negative Role of Surface Plasmons in the Transmission of Metallic Gratings with Very Narrow Slits

Abstract: To cite this version:Qing Cao, Philippe Lalanne. Negative role of surface plasmons in the transmission of metallic gratings with very narrow slits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
336
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 551 publications
(356 citation statements)
references
References 18 publications
18
336
2
Order By: Relevance
“…However, the transfer matrix formalism and the FDTD method are computationally very demanding [15]. In contrast, the RCWA and the EMA are the two closely related numerical techniques which are widely used to analyze 1D structures [2,3,5,6,8,16]. The RCWA expresses the dielectric function of the overall grating structure and the Electromagnetic (EM) field inside the grating region (−h ≤ z ≤ 0, see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the transfer matrix formalism and the FDTD method are computationally very demanding [15]. In contrast, the RCWA and the EMA are the two closely related numerical techniques which are widely used to analyze 1D structures [2,3,5,6,8,16]. The RCWA expresses the dielectric function of the overall grating structure and the Electromagnetic (EM) field inside the grating region (−h ≤ z ≤ 0, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical approaches of modeling EOT devices include the transfer matrix formalism [1,5,10,11], the Finite Difference Time Domain (FDTD) method [9,12], the Rigorous Coupled Wave Analysis (RCWA) [3,6,8,13], and the Exact Modal Analysis (EMA) [14]. Both the transfer matrix and FDTD methods solve Maxwell's equations directly using grids and produce accurate results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works have explained in detail the various optical and surface plasmon modes ͑SPs͒ that exist in these structures and their relative roles in producing the optical characteristics mentioned above. [9][10][11][12] Several works analyzed the relative roles of different types of SPs ͓i.e., horizontally oriented SPs ͑HSPs͒ on top and bottom air/metal interfaces, and coupled, vertically oriented SPs on the vertical walls of opposite sides of the grooves that undergo a Fabry-Perot resonance ͑VSP-CMs͔͒ in producing enhanced transmission and absorption. Most of the works concluded that VSP-CMs, Rayleigh anomalies and waveguide modes are the modes primarily responsible for these phenomena in 1D transmission gratings, not HSPs.…”
mentioning
confidence: 99%
“…Most of the works concluded that VSP-CMs, Rayleigh anomalies and waveguide modes are the modes primarily responsible for these phenomena in 1D transmission gratings, not HSPs. [10][11][12] In fact, it has now been shown both theoretically 5 and experimentally 12 that enhanced transmission occurs just as strongly in 1D transmission gratings with light polarized with the electric field oriented parallel to the surfaces of the metal wires ͑i.e., s-polarized light͒, a polarization that does not excite SPs. Most of the research on phase resonances has been done on 1D periodic transmission and diffraction gratings with light polarized with the magnetic field oriented parallel to the metal wires ͑i.e., p-polarized light͒.…”
mentioning
confidence: 99%